Determination of Per Capita Water Consumption and Domestic Wastewater Production in District 4, Tehran - Edris Hasanzadeh; Nilufar Mardaneh; Najmeh Ebrahimi; Shaghaiegh Shafighi; Mehdi Safari; Mahmoud Taghavi (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: One of the water resource management strategies is to accurately determine the per capita water consumption in various sectors, especially the drinking and sanitary sector. Therefore, the present study aimed to determine the per capita water consumption by field calculation and data collection from District 4 of Tehran subscribers who supply their water from the distribution network covered by the water and sewage company. In addition, the per capita wastewater production and the amount of biodegradable organic matter were estimated. Methods: In this study, the statistical population was the subscribers of Water and Wastewater Company, District 4 of Tehran, with 108603 subscribers from 2018-2020. Residential per capita water use is calculated by dividing the total volume of water sold to residential accounts by the number of people being served. The cost per water was calculated using the water tariff and the price per cubic meter of water. Results: Per capita water consumption for 2018, 2019, and 2020 were 172.33, 131, and 117.33 L/pd, respectively. The maximum and minimum per capita water consumption were obtained in May and April 2019, respectively (2576218 m3/month.S VS 677246 m3/month.S). In addition, the cost per water (in Rial/m3.month) for 2018, 2019, and 2020 were calculated as 145675, 164520 and 223944 respectively. Conclusion: The results demonstrated that the highest rate of water consumption and wastewater production pertained to April and May. As the cost of water consumption showed, it can be concluded that water prices are not an effective tool to reduce water consumption.